Romance e fragmentação: a escrita-viagem de Alice em Quarenta Dias (2014), de Maria Valéria Rezende - Modesto, Andreza Braga (2023)
This dissertation proposes a study of the work Quarenta dias (2014), by Maria Valéria Rezende, with the objective of examining aspects of the novel such as the fragmentation of the narrative, paying attention to the analysis of travel literature, as well as investigating what it means for the author to write the fictional text the way it is experienced. In the work, the author flirts with the intersection between the travel report and the writing of a diary resulting in the writingjourney of the protagonist who moves from Paraíba to Rio Grande do Sul and begins to build, through images of the city and the montage of fragments, the look practiced by the travelercartographer. To account for this configuration of the novel, we extend the discussion to some phenomena outlined in modern prose. The starting point is to analyze the protagonist inserted in the narrative spatiality, such as her cartographic nature moved by the processes of subjectivation and her relationship with the social and cultural context. Methodologically, the research is of a qualitative nature, based on literary analysis and anchored in the bibliographicexploratory method. The data collection instruments took into account the novel, as an essential element, in the light of the main theoretical supports for analysis such as Erwin Rosenthal (1975), Linda Hutcheon (1991), Milan Kundera (2016), Perrone-Moisés (1998), Walter Benjamin (2020), Willi Bolle (2022), Roland Barthes (2018), Modesto Carone (1974), Sergei Eisenstein (2002), Octávio Ianni (2000), Béatrice Didier (1976), and Yi-Fu Tuan (1980 and 2015).